Brazilian Consensus Meeting on Pediatric Hematopoietic Stem Cell Transplantation for Acquired Aplastic Anemia and Inherited Bone Marrow Failure Syndromes: HCT for Acquired Aplastic Anemia and Inherited Bone Marrow Failure Syndromes - Darrigo Junior, Luiz Guilherme; Loth , Gisele; Scheinberg, Phillip; Hallack Atta , Elias; Bonfim, Carmem (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2021)
THE BRAZILIAN SOCIETY FOR BLOOD AND MARROW TRANSPLANTATION (SBTMO) PRESENTS THE BRAZILIAN GUIDELINES ON HEMATOPOIETIC STEM CELL TRANSPLANTATION FOR ACQUIRED APLASTIC ANEMIA AND INHERITED BONE MARROW FAILURE SYNDROMES